Comparative analysis of iterative reconstruction algorithms with resolution recovery and new solid state cameras dedicated to myocardial perfusion imaging. (September 2017) - Brambilla, Marco; Lecchi, Michela; Matheoud, Roberta; Leva, Lucia; Lucignani, Giovanni; Marcassa, Claudio; Zoccarato, Orazio
Highlights: The new IRR algorithms and solid state SPECT improve resolution and contrast. They allow shorter acquisition time and lower tracer activities. The use of specific normal reference limits is recommended in perfusion quantification. There is a lack of conclusive evidence regarding the accuracy of LVEF determination. Abstract: New technologies are available in myocardial perfusion imaging. They include new software that recovers image resolution and limits image noise, multifocal collimators and dedicated cardiac cameras in which solid-state detectors are used and all available detectors are constrained to imaging just the cardiac field of view. These innovations resulted in shortened study times or reduced administered activity to patients, while preserving image quality. Many single center and some multicenter studies have been published during the introduction of these innovations in the clinical practice. Most of these studies were lead in the framework of "agreement studies" between different methods of clinical measurement. They aimed to demonstrate that these new software/hardware solutions allow the acquisition of images with reduced acquisition time or administered activity with comparable results (as for image quality, image interpretation, perfusion defect quantification, left ventricular volumes and ejection fraction) to the standard-time or standard-dose SPECT acquired with a conventional gamma camera and reconstructed with the traditional FBP method, considered as the gold standard. The purpose of this review is to provide the reader with a comprehensive understanding of the pro and cons of the different approaches summarizing the achievements reached so far and the issues that need further investigations.